Methods for modeling public policy and investment impacts on the economy, natural capital and ecosystem services - Onil Banerjee; Neville Crossman; Renato Vargas; Luke Brander; Peter Verburg; Martín Cicowiez; Jennifer Hauck; Emily McKenzie (Inter-American Development Bank (IDB), 2020)
The year 2020 is a critical year for sustainable development policy and practice with the review and renewal of various international commitments including the Sustainable Development Goals, the Convention on Biological Diversity and the Paris Agreement. The post-2020 agenda needs to be informed by more robust analytical approaches that capture the interactions between the economy, society and the environment. In this paper, we review the state of the art in available models and datasets that lay the groundwork for future analytical work to inform this agenda. Based on this review, we propose an integrated modeling approach for global analysis to underpin international policy discourse and advocacy, and; a sub-global approach focusing on evaluating specific strategies and policy portfolios to make progress toward sustainability commitments considering detailed local country context. Both approaches rely on integrating whole of economy computable general equilibrium models with spatial land use land cover and ecosystem services models. Endogenizing feedbacks between modeling system components ensures that evidence is based on interactions between all system components. Recent advances in methods, data and available tools discussed herein reduce barriers to entry for this type of complex systems analysis and increases the timeliness of policy advice.
Keywords: Q; D58; D6; I3; O; 330; natural capital; biodiversity; ecosystem services; integrated economic-environmental modeling; The IEEM Platform; GTAP; computable general equilibrium (CGE) modeling; ecosystem services modeling; land use land cover (LULC) c hange modeling